Kepemimpinan Kepala Sekolah Serta Motivasi Penggunaan Hijab Siswi di Sekolah - Al Husna Yusuf; Samsu Samsu; Hidayat Hidayat (Journal of Educational Research, 2023)
This study aims to provide an analysis of the principal's leadership and the motivation for the use of the hijab as well as the implementation of student behavior at the School. This study is important to explore the leadership of the principal and the motivation for the use of the female student hijab in depth in order to find the right solution in terms of the implementation of education, especially in terms of the leadership of the principal and the motivation for the use of the female hijab in several public schools, especially at the high school level. The method used is a qualitative approach. The determination of the subjects was carried out by snowball sampling techniques, namely the principal, Islamic religious education teachers, and class X students. Data collection techniques include in-depth interviews, observations, and documentation. After the data is collected, it is then analyzed using domain analysis techniques, components and taxonomy. In order to obtain valid and valid information, in this study, several techniques were used to test the validity of data, namely discussions with peers, extension of research time and data triagulation techniques. Penelitian ini bertujuan untuk memberikan analisis tentang Kepemimpinan Kepala Sekolah Serta Motivasi Penggunaan Hijab Siswi Dalam Implementasi Terhadap Perilaku di Sekolah. Kajian ini penting dilakukan guna mengeksplor kepemimpinan kepala sekolah dan motivasi penggunaan hijab siswi secara mendalam guna menemukan solusi yang tepat dalam hal pelaksanaan pendidikan terkhusus dalam hal kepemimpinan kepala sekolah dan motivasi penggunaan hijab siswi di beberapa sekolah umum terutama pada tingkat sekolah menengah atas . Metode yang digunakan adalah pendekatan kualitatif. Penentuan subjek dilakukan dengan teknik snowball sampling, yaitu kepala sekolah, guru pendidikan agama Islam, serta siswa kelas. Teknik pengumpulan data berupa wawancara mendalam, observasi, serta dokumentasi. Setelah data di kumpulkan kemudian di analisis menggunakan teknik analisis domain , komponensial dan taksonomi. Agar memperoleh informasi yang valid dan sah, dalam Penelitian ini di gunakan beberapa teknik pengujian keabsahan data, yaitu diskusi dengan teman sejawat, perpanjangan waktu penelitian dan teknik triagulasi data.